Translating and interpreting orality - Calvo Rigual, Cesáreo; Spinolo, Nicoletta (MonTi Monografías de Traducción e Interpretación, 2018)
The concept of orality is introduced in a broad sense, and then discussed in relation with translation, a relatively recent field. The first part of the paper analyses the role of orality in audiovisual translation (with the fundamental concept of prefabricated orality) and in written translation (especially for literature, theatre and comics), as well as the importance of certain linguistic elements (discourse markers, interjections and onomatopoeias) in reproducing orality. The second part of the paper, on the other hand, analyses the presence of the oral element in interpreting, where it obviously covers a pivotal role. Some of the many aspects that could be taken into account, and that are presented here, are prosody (intonation and voice, fluency and disfluency) and speech rate.